The Assessment of Low Intensity Complex Heritage Landscapes. The Case Study of Sancti Petri (Cádiz) - Rey-Pérez, Julia; Sánchez-Montañés, Benito; de la Fuente Peñalver, Agostina (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
There are areas where heritage elements are not associated with the common idea of heritage, which increases their invisibility and lack of protection. The aim of this research is to recognise the existence of these heritage environments known as Low Intensity Complex Heritage Landscapes (LICHL), through the case study of Sancti Petri. The proposed methodology firstly identifies the attributes that make up the heritage reality of this place, in order to subsequently address its valuation and the definition of its heritage intensity in terms of the relationship between all its factors. Secondly, it identifies the structure and density of the heritage reality, with the elaboration of maps, being able to justify whether it is a LICHL. The results reveal the number of heritage attributes that characterise the environment and its relationships, which reveals the difficulty of its management and the absence of regulatory figures for its protection.